METAFORA RISK AND RETURN SEBAGAI DASAR PENGEMBANGAN BAITUL MAAL WA TAMWIL (BMT) YANG MANDIRI - Tyas D. Hascaryani; Asfi Manzilati; Nurman S. Fadjar (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2011)
The purpose of this study is to find out how Baitul Maal Wa Tamwil (BMT) candevelop their independence as microfinance institutions, based on the expansion ofthe nature and development (metaphor) risk & return. With post positivism rational-istic approach, the results of this study are: (1) the risk faced by BMT in addition tofinancial risk (conventional), as well as more broadly in the form of guaran-tees(goodwill) and guarantee facilities of customer funds. 2) On the return, in addi-tion to financial return (conventional) the meaning has expanded on customer loyalty,market expansion and social functioning of the BMT.Keywords: metaphor, risk, return, independency